Development of Efficient Photovoltaic Solar Cells’ Various Models - Abu Baker, Aya (Aya Mahmoud Abu Baker, 2019)
This thesis deals with three different types of photovoltaic (PV) cells namely monocrystalline silicon and polycrystalline silicon and organic PV cells. We studied four models of PV cells equivalent circuits for each of mono- and polycrystalline silicon cells by QUCS software. The input parameters were extracted from the datasheet of the cells. The main goal of this research is to conclude the most efficient model of DC PV cells that gives the highest maximum power point. This work also deals with the main factors affecting the behavior of the PV cell: the cell temperature and solar irradiance. I-V characteristic curves will be drawn properly under the variation of temperature and irradiance. Depending on varying the models of PV cells, cell temperature and irradiance we saw how efficiency and different parameters of the cell will be varied. This thesis opens up a new field which is the organic solar cells devices or third generation of PV cells devices. The electrical simulation of an organic bulk heterojunction (BHJ) PV cell based on P3HT:PCBM as an active layer was done using GPVDM software under STC. The conversion efficiency of organic BHJ cells is studied under changing the thickness of the active layer. Furthermore, the current density-voltage characteristics were obtained under changing series resistance value. The simulation results confirmed, as expected, that monocrystalline silicon solar cells are more efficient than polycrystalline silicon solar cells but polycrystalline solar cells have higher quality than monocrystalline solar cells. It was concluded also that the non-crystalline solar cells are not as efficient as the crystalline ones but they are cheaper.
Keywords: Development of Efficient Photovoltaic Solar Cells’ Various Models